2004
DOI: 10.1002/mnfr.200400033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermal food processing on the chemical structure and toxicity of fumonisin mycotoxins

Abstract: Fumonisins are Fusarium mycotoxins that occur in corn and corn-based foods. They are toxic to animals and at least one analogue, fumonisin B1, is carcinogenic to rodents. Their effect on human health is unclear, however, fumonisins are considered to be risk factors for cancer and possibly neural tube defects in some heavily exposed populations. It is therefore important to minimize exposures in these populations. Cleaning corn to remove damaged or moldy kernels reduces fumonisins in foods while milling increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
0
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(114 citation statements)
references
References 106 publications
(120 reference statements)
2
107
0
5
Order By: Relevance
“…However, FB 1 was detected at the concentration ranging from 0.21 to 0.27 μg/g in 6 of 12 (50%) corn grit samples (Table 3). Our results showed that less or no contamination of fumonisin was found in the processed corn products, which is coincident with previous reports ( [Weidenbörner, 2001] and [Humpf and Voss, 2004]). Several previous studies were conducted to investigate the effect of processing method on fumonisn content.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…However, FB 1 was detected at the concentration ranging from 0.21 to 0.27 μg/g in 6 of 12 (50%) corn grit samples (Table 3). Our results showed that less or no contamination of fumonisin was found in the processed corn products, which is coincident with previous reports ( [Weidenbörner, 2001] and [Humpf and Voss, 2004]). Several previous studies were conducted to investigate the effect of processing method on fumonisn content.…”
Section: Resultssupporting
confidence: 93%
“…Cleaning corn to remove damaged or moldy kernels reduces fumonisins in foods while milling increases their concentration in some and reduces their concentration in other products (Jackson & Jalonski, 2004). Humpf and Voss (2004) found that baking, frying, and extrusion cooking of corn at high temperatures (≥190 °C) also reduced fumonisin concentrations in foods, with the amount of reduction achieved depending on cooking time, temperature, recipe, and other factors. It was also suggested that the fumonisin level in corn-based products was reduced during processing because fumonisins become 'hidden' and not recoverable under currently used extraction/purifi cation procedures (Kim, Scott, & Lau, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Our estimate is somewhat higher than intake levels estimated in the United States but lower than those in South Africa (39). It is noteworthy that the nixtamalization process by which maize is boiled in a lime solution to produce masa for tortillas is known to reduce the fumonisin level up to 80% (34,40,41). According to De la Campa et al's (34) observation in four small scale tortilla companies, FB1 can be reduced to undetectable levels in tortillas made from maize contaminated with FB1 at 0.6 to 1.6 ppm.…”
Section: Discussionmentioning
confidence: 99%
“…Fumonisins (FBs) are a group of secondary metabolites produced by micro fungi of the genus Fusarium and particularly by the F. verticillioides that is associated with maize and foods and feeds based on maize [92]. Out of the more than 15 FBs isomers that have been described so far, fumonisins B1 (FB1), B2 (FB2), and B3 (FB3) are the most abundant and frequent in the analyzed samples.…”
Section: Fumonisinsmentioning
confidence: 99%